Effect of Crude Leaf Extracts on Colletotrichum gloeosporioides (Penz.) Sacc. - Prapassorn Bussaman; Piyarat Namsena; Paweena Rattanasena; Angsuman Chandrapatya (Psyche: A Journal of Entomology)
Colletotrichum gloeosporioides (Penz.) Sacc. is a fungus that causes anthracnose disease in tropical fruit plants, resulting in damages of the fruit plants and low yield and quality of fruits. The use of chemical fungicides is common for management of this disease, but it also results in the development of fungal resistance to the chemicals. Therefore, this study aims to in vitro evaluate the efficacy of 14 crude leaf extracts against C. gloeosporioides. The results showed that Piper sarmentosum leaf extracts, using 80% of ethanol, methanol, and chloroform as solvents, were found to have very high antifungal activities. Crude methanol extract of P. sarmentosum leaves could effectively inhibit the growth of fungal mycelium (100%), followed by crude chloroform extract (81.85%) and 80% ethanol extract (45.50%). Maximum inhibition of C. gloeosporioides spore germination could be obtained after application with crude methanol extract of P. sarmentosum leaves and crude chloroform extract of Mentha cordifolia leaves at 1.25 and 2.5%, respectively. In conclusion, crude extracts of P. sarmentosum leaves were found to be highly effective for inhibiting both C. gloeosporioides mycelium growth and spore germination, and they have a potential as the new natural fungicides for management of anthracnose disease.